(untitled) (World Bulletin of Public Health, 2022)
This paper aims to describe outcomes of underlying musculoskeletal diseases and rheumatic with COVID-19 of children in Iraq. A retrospective study was conducted in different hospitals in Iraq for the period from 2-7-2020. To 9-6-2021, when 600 children were included in this study, they were distributed into two groups: Not hospitalised for 550 patients with 91.6% and hospitalised for 50 patients with 8.33% 600 CYP with RMDs <19 years old from Iraq with SARS-CoV- 2 infection were included, the majority with juvenile idiopathic arthritis for 300(50%) in group Not hospitalised and 33(5.5%) of group Hospitalised. seven of these patients died Compared with JIA, and the diagnosis of systemic lupus erythematosus distributed to 5 boys and two girl’s patients